Explaining the size and nature of response in a survey on health status and economic standard - Fredrik Johansson; Anders Klevmarken (Uppsala University, Department of Economics, 2006)
Using rich register data to analyze response behavior in a survey on health and economic standard, a model to explain contact and participation probabilities is estimated. A main result is that both probabilities are lower among respondents out of the labor market, who are immigrants and on benefits.
urn:nbn:se:uu:diva-83065
Keywords: C34; C42; J14; 330; Nonresponse; Response process; Befragung; Sozialpsychologie; Gesundheit; Einkommen